Media Teknologi sebagai Sarana Dakwah Digital: Analisis Sistematis Penggunaan Presentasi Digital dan Internet - Muhammad Faisal (Program Studi Komunikasi dan Penyiaran Islam, 2025)
This study examines the effectiveness of technological media in digital da'wah, focusing on digital presentations and internet platforms as innovative communication tools. The method employed is a Systematic Literature Review (SLR) to analyze relevant indexed literature, with inclusion criteria comprising articles and publications on digital da'wah published within the last five years. Exclusion criteria include studies that are irrelevant or inaccessible in full text. The results indicate that digital presentation applications such as Canva and Prezi enhance the appeal and effectiveness of da'wah messages through engaging and structured visual elements. Furthermore, the internet as a da'wah platform offers extensive opportunities to reach a global audience, despite challenges such as hoaxes and negative comments. Compared to traditional methods, digital media enables more responsive interaction and systematic message dissemination. This study highlights the importance of digital literacy for da'i in optimizing the use of technological media in da'wah. The practical implication of this research is the need to develop relevant digital strategies to enhance the effectiveness of da'wah in the digital era.